The Sound of William Barnes's Dialect Poems: 1. Poems of Rural Life in the Dorset Dialect, first collection (1844) - L Burton, T (University of Adelaide Press, 2013)
This series, developed from Tom Burton's groundbreaking study, William Barnes's Dialect Poems: A Pronunciation Guide (The Chaucer Studio Press, 2010), sets out to demonstrate for the first time what all of Barnes's dialect poems would have sounded like in the pronunciation of his own time and place. Every poem is accompanied by a facing-page phonemic transcript and by an audio recording freely available from this website.